2021
DOI: 10.1111/jfpp.15650
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of total, soluble, and insoluble dietary fiber from potato ( Solanum tuberosum ) residues and comparative evaluation of their structural, physicochemical, and functional properties

Abstract: The structural, physicochemical, and functional characteristics of total dietary fiber (TDF), insoluble dietary fiber (IDF), and soluble dietary fiber (SDF) isolated from potato residues were investigated. Potato dietary fiber consisted of IDF (73.18 g/100 g) and SDF (19.60 g/100 g); the main components were cellulose (42.93%) and pectin (27.82%), while lignin content was the lowest (5.74 g/100 g). The SDF contained much more rhamnose and galacturonic acid, whereas the major monosaccharide in IDF was glucose. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Sehingga kondisi bahan baku tetap terjaga dan mudah untuk diaplikasikan pada berbagai jenis olahan seperti kue, makanan bayi, ataupun makanan sehari-hari berbahan dasar kentang [7]. Kentang mengandung 73.18g/100g serat tidak larut dan 19.60 g/100 g serat terlarut [8]. Total serat yang terdapat pada kentang akan berubah saat sudah diolah menjadi tepung yakni sebesar 10.6 g/100 g. Serat pada kentang bermanfaat untuk menunjang pengurangan glukosa postprandial serta berpengaruh juga terhadap kadar lipid dalam darah.…”
Section: Pendahuluanunclassified
“…Sehingga kondisi bahan baku tetap terjaga dan mudah untuk diaplikasikan pada berbagai jenis olahan seperti kue, makanan bayi, ataupun makanan sehari-hari berbahan dasar kentang [7]. Kentang mengandung 73.18g/100g serat tidak larut dan 19.60 g/100 g serat terlarut [8]. Total serat yang terdapat pada kentang akan berubah saat sudah diolah menjadi tepung yakni sebesar 10.6 g/100 g. Serat pada kentang bermanfaat untuk menunjang pengurangan glukosa postprandial serta berpengaruh juga terhadap kadar lipid dalam darah.…”
Section: Pendahuluanunclassified
“…Potatoes (Solanum tuberosum L.) are the fourth largest crop in the world after maize, wheat and rice (Waliullah, Mu, & Ma, 2021). China ranks first in global potato production, with 78 million tons processed in 2020, accounting for 21.79 % of the world's total potato production (FAO, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The potato residues are the by-products of potato starch processing. In particular, about 3 million tons of wet residues are produced annually (Waliullah et al, 2021). So far, only a small amount of potato residues are utilized as cheap animal feed, and most of them are thrown away, resulting in serious resource waste and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…During the enzymatic digestion, it shows the resistance capacity in the small intestine (Maphosa & Jideani, 2016). Based on water solubility, the total dietary fiber (TDF) can be sub‐categorized into insoluble dietary fiber (IDF) and soluble dietary fiber (SDF) (Huang et al, 2018; Jia et al, 2019; Waliullah et al, 2021). Many health significant diseases, including cardiovascular disease, type 2 diabetes, obesity as well as constipation and gastrointestinal disorders have been reduced with the intake of dietary fiber (Slavin, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…IDF in the food lowers transit time, as well as restricts the contact time of harmful substances with the intestinal walls (Kumari & Deka, 2021; Kurek & Wyrwisz, 2015). Various report suggested that the application of IDF in food processing industries use numerous emerging technologies to modify and enhance its physiochemical properties (Chen et al, 2013; Waliullah et al, 2021).…”
Section: Introductionmentioning
confidence: 99%